E-005 Single-center experience with neuroform atlas stent-assisted coiling of intracranial aneurysm. (22nd July 2018) - Ciccio, G; Robert, T; Smajda, S; Fahed, R; Blanc, R; Michel, P
Abstract : Purpose: Expandable stents have broadened the spectrum of endovascular treatment of intracranial aneurysms. The Neuroform ATLAS, a nitinol self-expanding, hybrid/open-cell stent, is the evolution of the Neuroform EZ, with enhanced navigability, and can be delivered through a low-profile 0.017 inch delivery catheter. We present our experience in the treatment of intracranial aneurysms with this stent. Material and methods: We prospectively maintained a database from consecutive patients in our institution who underwent stent-assisted coiling (SAC) with Neuroform ATLAS stent from July 2015 to December 2017. Clinical and angiographic results were analyzed. Results: Seventy-seven intracranial saccular aneurysms in 75 patients (51 women, 24 men, mean age=56 years old) were consecutively treated. The stent was used in 69 previously untreated aneurysms, and in 7 cases of aneurysmal recanalization. One single stent was used in 32 (42.1%) aneurysms while 44 (57.8%) aneurysms were treated with 2 stents (43 in 'Y' configuration, 1 in 'X' configuration). One case of Y stent-assisted coiling was interrupted prematurely because of aneurysm perforation during navigation. The post-treatment angiography showed a complete occlusion in 43 cases (56.5%), a neck remnant in 11 cases (14.4%) and an incomplete occlusion in 22 cases (28.9%). The overall complication rate was 11.7%. At last follow-up, five patients had a modified Rankin Scale score (mRS) >2 (6.5%), including 2 deaths (2.6%). Forty-five aneurysms had a radiological follow-up (mean follow-up duration: 10.9 months): 38 aneurysms (84.4%) were completely occluded, 6 aneurysms had a neck remnant (13.3%) and 1 aneurysm (2.2%) was uncompletely occluded. Conclusion: The Neuroform ATLAS stent is an effective device for treatment of complex intracranial aneurysms, allowing good conformability and high level of navigability, but with a non-negligible rate of complications. Disclosures: G. Ciccio: None. T. Robert: None. S. Smajda: None. R. Fahed: None. R. Blanc: None. P. Michel: None.